Chemistry of 2-cyanomethylene-4-thiazolidinone. (4th May 2017) - El-Gaby, Mohamed S. A.; Ammar, Yousry A.; El-Hag Ali, Gameel A. M.; Helal, Mohamed H. M.; Salem, Mohamed A.; Ghorab, Mostafa M.
ABSTRACT: This article is a brief review about the synthesis and chemistry of 2-cyanomethylene-4-thiazolidinone1 . The most significant applications of 4-thiazolidinone1 in heterocyclic synthesis are due to its two reactive methylenes. The endo-cyclic methylene protons are activated by the neighboring carbonyl moiety and the exo-cyclic methylene protons by the adjacent cyano group. Different types of reactions, such as alkylation, coupling, and Knoevenagel condensation, as well as cyclization reactions are illustrated for the synthesis of different classes of biologically important heterocyclic skeletons from this novel precursor. GRAPHICAL ABSTRACT: